DYNAMICS OF THE SHREW TAXOCENE STRUCTURE IN THE LATE QUATERNARY OF THE SOUTHERN FAR EAST - Nesterenko V.A.; Sheremetyev I.S.; Alexeeva E.V. (My University, 2002)
Fossil remains of 11 shrew species from the Bliznets cave (southern Primorie Region) are examined. The changes of shrew species composition from the Upper Pleistocene to the present days are traced. The relations between these changes and Holocene paleoclimatic events are considered. The structural features and the patterns of the modification of the early shrew taxocenes are investigated. A hypothetical model for the formation of multispecies assemblages is proposed.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная